1998
DOI: 10.1038/sj.bmt.1701235
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of spinal vs general anaesthesia in bone marrow harvesting

Abstract: Summary:Bone marrow harvesting (BMH) can be performed with either general (GA) or spinal anaesthesia (SPA). Whether SPA is advantageous in BMH and if this technique is safe for procedures performed in the prone position is still controversial. To evaluate the safety and efficacy of both anaesthetic techniques in BMH, 37 allogeneic donors (nine female, 28 male; 34.3 ؎ 9 years; ASA class 1-2) received either spinal (group 1, n = 20) or general anaesthesia (group 2, n = 17) according to their personal wishes. Und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0
2

Year Published

1999
1999
2019
2019

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 7 publications
2
8
0
2
Order By: Relevance
“…Autologous donors of BM, according to our data, needed more autologous and allogeneic blood transfusions than did allogeneic donors, and more autologous blood when BMH was carried out under GA rather than under RA (73 vs 40%, respectively). This is in accordance with data obtained by Burmeister et al 6 in a prospective study of 37 healthy allogeneic donors, in which no difference in blood requirements between the GA and RA groups was found.…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…Autologous donors of BM, according to our data, needed more autologous and allogeneic blood transfusions than did allogeneic donors, and more autologous blood when BMH was carried out under GA rather than under RA (73 vs 40%, respectively). This is in accordance with data obtained by Burmeister et al 6 in a prospective study of 37 healthy allogeneic donors, in which no difference in blood requirements between the GA and RA groups was found.…”
Section: Discussionsupporting
confidence: 82%
“…Similar findings have been reported by others while comparing GA with RA for BMH, as well as for another surgical procedures. 6,7,11,13,14 In an earlier retrospective study of 162 BM donations (63 allogeneic and 99 autologous), Lavi et al 4 found that patients who underwent GA required more RBC units than those undergoing RA. Our results do not confirm this finding.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations